Higher Efficiency of Percutaneous Microwave (MWA) Than Radiofrequency Ablation (RFA) in Achieving Complete Response in Cirrhotic Patients with Early Hepatocellular Carcinoma - Silvia Gaia; Michela Ciruolo; Davide Giuseppe Ribaldone; Emanuela Rolle; Enrica Migliore; Elena Mosso; Simone Vola; Alessandra Risso; Sharmila Fagoonee; Giorgio Maria Saracco; Patrizia Carucci (Current Oncology, 2021)
Background: Contrasting data are available in the literature regarding the superiority of percutaneous microwave ablation (MWA) or radiofrequency ablation (RFA) in very early or early (BCLA 0 or A) hepatocellular carcinoma (HCC). Aims: The primary outcome was to compare the efficacy of RFA and MWA in achieving complete response in cirrhotic patients with early and very early HCC. The secondary outcomes were to evaluate the overall survival and the recurrence rate. Methods: A retrospective, observational, single-center study was performed. Inclusion criteria were liver cirrhosis, new diagnosis of a single node of HCC measuring a maximum of 50 mm or up to three nodules with diameter up to 35 mm, treatment with RFA or MWA. Radiological response was evaluated with multiphasic contrast-enhanced Computed Tomography or Magnetic Resonance Imaging at 5–7 weeks after thermal ablation. Complete response was defined when no vital tissue was detected after treatment. Results: Overall, 251 HCC patients were included in this study; 81 patients were treated with MWA and 170 with RFA. The complete response rate was similar in MWA and RFA groups (out of 331 nodules, 87.5% (91/104) were treated with MWA and 84.2% (186/221) were treated with RFA, p = 0.504). Interestingly, a subanalysis demonstrated that for 21–35 mm nodules, the probability to achieve a complete response using MWA was almost 5 times higher than for RFA (OR = 4.88, 95% CI 1.37–17.31, p = 0.014). Moreover, recurrence rate in 21–35 mm nodules was higher with RFA with respect to MWA (31.9% versus 13.5%, p = 0.019). Overall survival was 80.4% (45/56) when treated with MWA and 62.2% (56/90) when treated with RFA (p = 0.027). No significant difference was observed between MWA and RFA treatment in the 15–20 mm nodules group. Conclusion: This study showed that MWA is more efficient than RFA in achieving complete response in HCC nodules with 21 to 35 mm diameter.